Analysis of the incidence of infectious pancreatic necrosis mortality in pedigreed Atlantic salmon, Salmo salar L., populations - Guy, Derrick R; Bishop, Stephen C; Brotherstone, Sue; Hamilton, Alastair; Roberts, Ronald J; McAndrew, Brendan; Woolliams, John A (Journal of Fish Diseases, 2006)
A total of 77 124 Atlantic salmon post-smolts, representing 197 full-sib families produced by 149 males and 197 females, experienced a field challenge from infectious pancreatic necrosis virus (IPNV), following transfer to three separate seawater sites. The first IPN mortality was observed 45 days after transfer, and the duration of the epidemic varied between 37 and 92 days among sites. Mortalities were traced to their parental families by PIT (Passive Integrated Transpondes) tag records and DNA genotyping. Full-sib family mean incidence of mortality was calculated for each family on each site. Heritabilities were estimated based on the heterogeneity of chi-square using incidence within half-sib families and the variance in incidence among full-sib families, both on the observed and underlying liability scale. The observed correlation among families across sites was used to estimate genetic correlations. The overall mortality rate was 10.8%, with only small differences between sites, ranging from 10.3% to 11.9%. Heritabilities on the liability scale were found to be moderate to strong, and ranged between 0.24 and 0.81, with a pooled estimate of 0.43, greater than is typically associated with disease traits. Genetic correlations among sites were all substantial, between 0.71 and 0.78, and indicated that a substantial component of the genetic variation displayed within sites was common to all. The results show that field challenges can yield very good genetic information on family differences in resistance, especially when replicated over sites, which may then be developed for use in selection for breeding strains of Atlantic salmon with greater resistance to IPN.